2022
DOI: 10.1172/jci.insight.157031
|View full text |Cite
|
Sign up to set email alerts
|

Durability of ChAdOx1 nCoV-19 vaccination in people living with HIV

Abstract: Oxford University has entered into a partnership with AstraZeneca for further development of ChAdOx1 nCoV-19 (AZD1222). AstraZeneca reviewed the data from the study and the final manuscript before submission, but the authors retained editorial control. SCG is cofounder of Vaccitech (a collaborator in the early development of this vaccine candidate) and named as an inventor on a patent covering use of ChAdOx1vectored vaccines (PCT/GB2012/000467) and a patent application covering this SARS-CoV-2 vaccine. TL is n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 69 publications
5
33
0
1
Order By: Relevance
“…Though our data is limited by the relatively low number of patients in our cohort and further studies will be needed to determine the impact of lower CD4 þ T-cell counts on the vaccine response, we demonstrate that virally suppressed PWH with high CD4 þ counts generate robust humoral and cellular immune responses. Our results are consistent with a recent report that showed similar rates of decay of immune responses in PWH and healthy donors following ChAdOx1 nCoV-19 vaccinations [14]. Our data shows that similar to healthy donors, virally suppressed PWH with high CD4 þ T-cell counts have persistent SARS-CoV-2-specific T-cell responses at 6 months postvaccination despite a modest decline from the peak levels measured shortly after vaccination.…”
supporting
confidence: 92%
“…Though our data is limited by the relatively low number of patients in our cohort and further studies will be needed to determine the impact of lower CD4 þ T-cell counts on the vaccine response, we demonstrate that virally suppressed PWH with high CD4 þ counts generate robust humoral and cellular immune responses. Our results are consistent with a recent report that showed similar rates of decay of immune responses in PWH and healthy donors following ChAdOx1 nCoV-19 vaccinations [14]. Our data shows that similar to healthy donors, virally suppressed PWH with high CD4 þ T-cell counts have persistent SARS-CoV-2-specific T-cell responses at 6 months postvaccination despite a modest decline from the peak levels measured shortly after vaccination.…”
supporting
confidence: 92%
“…The selection procedure is summarized in Figure 1 . Overall, 22 studies were included for meta-analysis of seroconversion rates ( Table 1 ) ( Antinori et al, 2022 , Bergman et al, 2021 , Brumme et al, 2022 , Feng et al, 2022 , Frater et al, 2021 , Heftdal et al, 2022 , Huang et al, 2022 , Jedicke et al, 2021 , Khan et al, 2021 , Levy et al, 2021 , Lombardi et al, 2022 , Lv et al, 2022 , Madhi et al, 2021 , Madhi et al, 2022 , Netto et al, 2022 , Ogbe et al, 2022 , Rahav et al, 2021 , Schmidt et al, 2022 , Tuan et al, 2022 , Woldemeskel et al, 2021 , Zeng et al, 2022 , Zou et al, 2022 ). Tables S1 and S2 present the serological antibody titers after a first and second dose of COVID-19 vaccines, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In one study, BNT162b2, mRNA-1273 and AZD1222 were used simultaneously ( Brumme et al, 2022 ). Among the viral vector vaccines, AZD1222 was used in 4 (18%) studies ( Brumme et al, 2022 , Frater et al, 2021 , Madhi et al, 2021 , Ogbe et al, 2022 ) and as the sole vaccine in 3 (14%) ( Frater et al, 2021 , Madhi et al, 2021 , Ogbe et al, 2022 ), and Ad26.COV2.S was used in only one (5%) study ( Khan et al, 2021 ). Therefore AZD1222 featured more prominently.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study of ART-suppressed PLWH who received the BNT162b2 vaccine showed lower neutralizing responses compared to healthcare workers, but the cohort did not represent the full spectrum of HIV disease, follow-up was limited to 18 days, and no T cell assays or mechanistic studies were performed [61]. Although a cohort of PLWH receiving the ChAdOx1 vaccine did not find differences in humoral and ELISPOT and T-cell responses compared to healthy controls over 6 months of follow-up, the cohort was relatively young and healthy, and excluded individuals with CD4 + T-cell counts < 350 cells/µL or virologic non-suppression [62,63]. A cohort of 100 PLWH matched on age, sex, which mRNA vaccine they received, and time since vaccination demonstrated greater surrogate virus neutralization test non-response among PLWH, with greater non-response among those with CD4 + T-cell count < 200 cells/µL and unsuppressed viral loads [64].…”
Section: Protection From Sars-cov-2 Vaccinationmentioning
confidence: 99%